A two-stage power converter for welding applications with increased efficiency and reduced filtering - Klumpner, Christian; Corbridge, Mathew (2008)
The power supply technology used in welding applications changed dramatically from manually tap-controlled 50Hz bulky transformers which had large leakage inductance to provide stable arc burn to switch-mode fast controlled highfrequency power electronics. Nowadays, the typical converter configuration consist of a diode rectifier supplying via a large electrolytic capacitor a smooth DC-link voltage to a high switching frequency H-bridge inverter that steps down the voltage and provides isolation via a high frequency transformer whilst operating with adjustable dutycycle to maintain the output current constant. This topology allows for important size reduction since the size of magnetics decreases rapidly with the increase of the frequency. This paper proposes a more complex two-stage configuration with a buck DC/DC converter operating at a reduced switching frequency to feed adjustable voltage to an H-bridge inverter, which is operating always with the required voltage at 50% dutycycle, enabling in addition the minimization of the output filter size and of the switching losses.